To determine the level of halal awareness among the residents of Kampung Tabuan Melayu, Kuching, Sarawak / Mohamad Azri Jos - Jos, Mohamad Azri (2014)
Awareness of halal products is gaining in popularity worldwide as more and more people become aware of the Islamic food requirements. This popularity is not only driven by the awareness amongst Muslims of the need that which is believed halal but also from manufacturers and suppliers who want to tap into lucrative Muslims markets. This research paper discuss about the user awareness at Kampung Tabuan, regarding halal products. Basically, the purpose of this research is to measure degree on user awareness of halal products. The researcher has conducted interview with respondents who cannot read the questionnaire that was provided. Besides, to investigate and gathered the information the questionnaire was distributed to consumers in Kampung Tabuan. Then, those data were analyzed and tabulated in form of bar chart and pie chart to get the clear picture of overall general and specific about halal products. Results show that majority of respondents are aware about the importance of using halal certification in food industry. The level of consumer awareness is high because consumers nowadays preferred halal product even if they are non-Muslims consumer; as they like to eat halal food products. The data is analyzed by using SPSS version 11.0 and Microsoft Excel. In addition, the hypothesis for this research is there are relationship between awareness of halal certification and their perception about the importance of halal certification implementation.